Experimental application of an automated alignment correction algorithm for geological CT imaging: phantom study and application to sediment cores from cold-water coral mounds - Skornitzke, Stephan; Raddatz, Jacek; Bahr, André; Pahn, Gregor; Kauczor, Hans-Ulrich; Stiller, Wolfram (European radiology experimental, 2019)
In computed tomography (CT) quality assurance, alignment of image quality phantoms is crucial for quantitative and reproducible evaluation and may be improved by alignment correction. Our goal was to develop an alignment correction algorithm to facilitate geological sampling of sediment cores taken from a cold-water coral mount.
Gesehen am 13.07.2021